2022
DOI: 10.18517/ijaseit.12.3.13637
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Risk of Rubber Prices Using the ARCH-GARCH and VaR Methods on Farm Income in West Aceh District

Abstract: The fluctuating price of rubber is often detrimental to farmers because farmers generally cannot manage the timing of the sale to get a profitable selling price. High price fluctuations provide opportunities for traders to manipulate price information on farmers and cause farmers not to enjoy the higher true price. This research aims to see how risky the price is received by rubber farmers and its effect on farm income in West Aceh District. This study uses the ARCH-GARCH method and VaR calculations for price … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In Indonesia, the natural rubber export price is affected by international rubber price, export tariff, exchange rate, domestic consumption, export volume, and global crisis affected (Al Kautsar, 2014;Daulika, Peng, & Hanani, 2020). At the farmer's level Arifin (2005), Masliani (2020); and Usman, Wardhana, & Istiqamah (2022) and indicated that changes in the international price of natural rubber at the processing level are not perfectly transmitted to farmgate price, especially when the price increase. The traders and rubber factories keep the profit from the price increase.…”
Section: Figure 1 Natural Rubber Farmgate and International Price Jan...mentioning
confidence: 99%
“…In Indonesia, the natural rubber export price is affected by international rubber price, export tariff, exchange rate, domestic consumption, export volume, and global crisis affected (Al Kautsar, 2014;Daulika, Peng, & Hanani, 2020). At the farmer's level Arifin (2005), Masliani (2020); and Usman, Wardhana, & Istiqamah (2022) and indicated that changes in the international price of natural rubber at the processing level are not perfectly transmitted to farmgate price, especially when the price increase. The traders and rubber factories keep the profit from the price increase.…”
Section: Figure 1 Natural Rubber Farmgate and International Price Jan...mentioning
confidence: 99%